Edukasi Penggunaan Antibiotik dan Analgesik yang Aman dan Tepat pada Anak SMK NU Sekaran - Susanti, Irma; Khurin’in, Laura Ayu; Aulia, Harica Karinina Rahma; Ichsan, Talitha Nathania; Faizah, Puspa Ayu; Syarifuddin, Ahmad Mighfar (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Background: Inappropriate use of antibiotics and analgesics among adolescents remains a public health concern, mainly due to self-medication practices and limited understanding of proper medication use principles, including DAGUSIBU (Get, Use, Store, Dispose). Low medication literacy may increase the risk of adverse effects and antimicrobial resistance. Objective: This community service activity aimed to improve students’ knowledge regarding the safe and appropriate use of antibiotics and analgesics at SMK NU Sekaran. Methods: The activity was conducted through interactive socialization and educational sessions supported by PowerPoint presentations and educational leaflets. The partner involved was SMK NU Sekaran. The improvement in knowledge was evaluated using a questionnaire consisting of 10 questions. Results: The mean pretest score was 7.62% and the posttest score was 8.76%, showing a statistically significant difference (p 0.001). The results indicated an increase in knowledge before and after the educational intervention.